Performance improvement in photosensitive organic field effect transistor by using multi-layer structure - Alpaslan Kösemen Z.; Kösemen A.; Öztürk S.; Canımkurbey B.; Erkovan M.; Yerli Y. (Elsevier B.V., 2019)
In this study, a new approach was introduced for Photo-OFETs as a multi-layer structure. Poly(3-hexylthiophene-2,5-diyl) regioregular (P3HT) and Copper(II) phthalocyanine (CuPc) thin films were used as two different active photo-absorber layers in the same device structure. Poly(methyl methacrylate) (PMMA) was used as a dielectric layer and all devices were fabricated with a top-gate bottom-contact configuration. In order to investigate the effect of the location of each layer on the Photoresponsive organic field-effect transistors (Photo-OFET) performance, five different devices in various structures were produced and analyzed. Surface properties of active layers have been investigated via Atomic Force Microscopy (AFM) and effects of surface roughness on device performance have been discussed. P3HT/CuPc/P3HT multi-layered structure exhibited the best performance in terms of photoresposivity(as 45 mA/W) and photosensitivity (~ 2 × 10 3 ). Photo-OFET based on a multi-layer structure demonstrated superior performance with wider absorbance spectrum region compared to conventional single component devices of P3HT or CuPc. The proposed multi-layer structure can be a model to improve the realization of high performance Photo-OFETs. © 2019 Elsevier B.V.
Keywords: Multilayer structure; Organic field effect transistors; Photoresponsive organic field-effect transistors; Photosensitivity; Poly(3-hexylthiophene); Poly(methyl methacrylate)